Learning Method Through Song In Memorizing Java Language Material In Ra Ar-Romaliyah Dusun Sli Bung Padas Village Padas District Ngawi - Ucik Binsa (Tajdid Al-Athfal, 2023)
The research in this thesis is motivated by the problems taken in this study, namely that children have difficulty memorizing Javanese language material so they must use the singing method in the learning process. This study aims to analyze the method of learning through songs in memorizing Javanese language material and the factors that underlie the use of the song method in memorizing Javanese language material. The research methodology used is qualitative research with data collection techniques using observation, interviews, and documentation. After the data is collected, analysis is carried out. The samples taken from this thesis are the head of RA AR-ROMALIYAH, class teachers and students of RA ArRomaliyah. The results of this study indicate. The application of the singing method to memorize the Javanese language has been carried out by selecting the appropriate song so that it is easily understood by children and habituation of the Javanese language is carried out every Friday. The introduction of Javanese language can teach children about manners and manners and one way to preserve Javanese culture.